(untitled) (Global Journal of Computer Science and Technology, 2011)
The goal of this paper is to evaluate the performance of the application developed with Mobile Ajax for mobile phones. The measurement of performance is conceived to be in two phases. At the first phase we measure and evaluate the performance of mobile browser using different Ajax toolkits. And at the second phase we measure and compare the performance of a Mobile Web Ajax application with a traditional mobile web application. In the end we propose some tips to solve the performance problem of those applications.